2004
DOI: 10.1016/j.febslet.2004.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a hTid‐1 mutation which sensitizes gliomas to apoptosis

Abstract: Human Tid-1 (hTid-1) is a DnaJ chaperone protein with homology to the Drosophila tumor suppressor Tid56. We report the first case of a tumor-associated mutation at the human TID1 locus, which was identified in the SF767 glioma cell line giving rise to aberrantly high levels of a hTid-1 L mutant variant. In this study, we set out to determine whether this change in hTid-1 status influences the response of glioma cells to adenoviral (Ad)-mediated delivery of the two major isoforms of TID1, hTid-1 L and hTid-1 S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
0
26
0
Order By: Relevance
“…Recently, Canamasas et al showed that loss of Tid1 expression was associated with human basal cell carcinoma but not with normal keratinocytes (4). Similarly, Trentin et al also reported a Tid1 mutation in human glioma cells and introduction of wild-type Tid1 into these cancer cells induced their apoptosis (5). These observations suggest that Tid1 plays a role in human carcinogenesis.…”
Section: Introductionmentioning
confidence: 74%
“…Recently, Canamasas et al showed that loss of Tid1 expression was associated with human basal cell carcinoma but not with normal keratinocytes (4). Similarly, Trentin et al also reported a Tid1 mutation in human glioma cells and introduction of wild-type Tid1 into these cancer cells induced their apoptosis (5). These observations suggest that Tid1 plays a role in human carcinogenesis.…”
Section: Introductionmentioning
confidence: 74%
“…There is a body of evidence indicating that hTid1 plays an important role in apoptosis and/or cell proliferation in various cell types (38,40). In addition, it was shown that hTid regulates apoptosis of glioma cells and suppresses growth of head and neck cancer cells both in vitro and in vivo (61,62). The mechanisms involved in hTid1-mediated growth suppression remain elusive because hTid1 modulates the activity of many proteins involved in signal transduction and hence in the survival/apoptosis and/or cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In MCJ, the J domain is located at the C-terminal unlike other DNAJ proteins where the J domain is at the N-terminal. In ovarian carcinoma, the expression of MCJ has been associated with enhanced sensitivity to paclitaxel, topotecan, and cisplatin [47]. Epigenetic inactivation of MCJ is reported in malignant pediatric brain tumors [69].…”
Section: Abstract Hsp40 á Dnaj á Cancermentioning
confidence: 99%
“…However, the recent flurry of activity in this emerging field is certainly noticeable. Reports describing the involvement of some HSP40 family members of distinct classes such as hTid I (class DNAJA3), HLJ1 (class DNAJB4) in modulation of tumor growth are opening new frontiers for studies on this family [45][46][47][48][49][50][51]. In the next few paragraphs, we will review the published research articles describing members of human HSP40 in cancer.…”
Section: Abstract Hsp40 á Dnaj á Cancermentioning
confidence: 99%
See 1 more Smart Citation